Ecclesial identification beyond late modern individualism? : a case study of life strategies in growing late modern churches - Tangen, Karl Inge. (Leiden : BRILL, 2012)
Why do people identify with growing late modern churches - and does identification lead to morally transforming commitments beyond late modern consumerism? This case study presents findings that may inspire both social scientists and theological practitioners to new forms of thinking.
6. Organisational Foci -- Why Do People Identify?
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Church growth -- Europe, Western -- Case studies; Identification (Religion) -- Case studies; RELIGION -- Christian Church -- Administration; Church growth; Identification (Religion); Europe, Western; Electronic books; Case studies